A Comparison and Contrast of The Roles of The Visual and Olfactory Senses in Cognitive Learning Process - Akpınar, Burhan; Ersözlü, Zehra Nur (Tokat Gaziosmanpaşa Üniversitesi, 2008)
In this manuscript, the roles of the visual and olfactory senses in learning process are taken in historical process. In the study, which is in the form of a suvaillance model, the roles of the visual and olfactory senses in cognitive learning process are taken into consideration in a comparative point of view. In the study, it is seen that, the visual culture gives the first place to visuality and turns the role the olfactory sense in learning process into being less important. However the researches point out that olfaction may have an important role in learning. Thus in the reseaches, it is proved that in the processes of spatial perception and attention, seeing, and in the process of memory, olfaction is more dominant. The results also showed that, the visual perception is electromagnetically coded, proportional, objective and quantitative, and the olfactory perception is chemically coded, holistic and qalitative. It is also determined that, the visual memory is semantic and the olfactory memory is incidental. In the study it is evaluated that, the sense of smell is not a rival to the visual sense, but more likely to be integral in increasing the quality of visual perception

Bu makelede, görme ve koklama duyularının öğrenme sürecindeki rolleri tarihi süreç içerisinde ele alınarak tartışılmıştır. Tarama modelindeki çalışmada, görme ve koklama duyularının bilişsel öğrenme sürecindeki rolleri karşılaştırmalı olarak ele alınmıştır. Çalışmada, görsel kültürün öğrenme sürecinde görmeyi ön plana çıkararak koku duyusunun bu süreçteki rolünü perdelediği belirlenmiştir. Ancak araştırmalar, koklamanın öğrenmede önemli bir role sahip olabileceğini göstermiştir. Nitekim yapılan karşılaştırmada uzaysal algı ve dikkat sürecinde görmenin; hafıza sürecinde ise koku duyusunun daha baskın olduğu belirlenmiştir. Ayrıca görsel algının elektromanyetik kodlu, oranlı, objektif ve nicel olduğu; kokusal algının ise, kimyasal kodlu, bütüncül, subjektif ve nitel olduğu belirlenmiştir. Ayrıca, görsel hafızanın anlamsal, kokusal hafızanın ise olaysal olduğu belirlenmiştir. Çalışmada, koku duyusunun görmeye rakip değil, değerlendirilmiştir
Görme ve Koklama Duyularının Bilişsel Öğrenme Sürecindeki Rollerinin Karşılaştırılması